Mapping Blackness in the Stacks: A Conversation with Dr. Dorothy Williams - Currie-Williams, Kelann; Rochat, Désirée (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2025)
Dr. Dorothy W. Williams is a prize-winning independent historian, archivist, and memory worker of Black Canada. She has published two monographs on Montreal’s Black community and has done extensive research on the history of Black print in Quebec during the 20th century — amongst other topics. Her research and public history efforts cannot, however, be dissociated from her decades-long collecting and archiving work — the focus of this edited interview. Over the years, she amassed an extensive archival collection of Black Montreal in her home and worked to preserve the archives of many Black institutions in the city. Following a bio-bibliographical approach, the interview examines the evolution of her collecting practices and their reciprocal relation with her scholarship and pedagogy.